Looking for the descendants of Great Mongol - Fando, Roman A. (The New Research of Tuva, 2014)
Comment on: Zakharov-Gezekhus I.A. In the footsteps of Genghis Khan. Geneticist in the center of Asia. Moscow; Izhevsk: Institute for computer studies, 2013. 84 p.